Characterisation of methane variability and trends from near-infrared solar spectra over Hefei, China. (January 2018) - Tian, Yuan; Sun, Youwen; Liu, Cheng; Wang, Wei; Shan, Changgong; Xu, Xingwei; Hu, Qihou
Abstract: This study presents the characterization of X CH4 (averaged-column dry air mole fraction) variability and trends using the near-infrared (NIR) solar spectra recorded by the ground-based high-resolution Fourier transform spectrometer (FTS) over Hefei, China. An annual increase of 10.55 ± 2.87 ppb yr −1 (0.56 ± 0.15% yr −1 ) in CH4 concentrations was deduced from the three years' worth of FTS measurements. Seasonal cycles and three typical diurnal variation modes were captured. The maximum CH4 concentration occurred in late summer or early autumn, while the minimum CH4 concentration occurred in winter. CH4 concentrations in August were 30–55 ppb higher than those in January. In most cases, the diurnal variability exhibited an increasing trend in summer or early autumn, while it exhibited a decreasing trend or remained relatively constant in other seasons. We compared the FTS data with the GOSAT data and the GEOS-Chem model data. The average difference between the GOSAT and FTS data (GOSAT minus FTS) was 1.60 ppb (0.09%) ±13.0 ppb (0.70%), and between the smoothed GEOS-Chem model data and FTS data (GEOS-Chem minus FTS) was −8.09 ppb (0.45%) ±17.83 ppb (0.95%). The differences between GOSAT and FTS were season-independent; however, obvious season-dependent differences were observed between GEOS-Chem and FTS. The GOSAT and GEOS-Chem models could reproduce the seasonal cycle observed by FTS with correlation coefficients (r) of 0.77 and 0.86, respectively. Highlights: Methane variability and trends were characterized with IFS125HR. The differences between GOSAT and FTS were independent of seasons. The differences between GEOS-Chem and FTS were season-dependent. Dominant contributors to annual increase in atmospheric CH4 were deduced.